Air Pollution in Wuhan, China: Source Apportionment of PM 2.5 and Source Identification of PM 2.5-Induced Oxidative Stress - Lu, Zhaojie (My University, 2018)
Abstract Particulate matter with aerodynamic diameter less than 2.5 μm (PM2.5) can enter human respiratory tract through inhalation and cause a series of adverse health effects. PM2.5 pollution issue in Wuhan, China, which is a major city in the central China, has been escalating in the past decades. PM2.5 samples were collected at three sites in Wuhan and were analyzed for their chemical compositions. To provide insights on the sources contributing to PM2.5 mass concentration as well as to the adverse health effects caused by PM2.5, source apportionment study and source identification of the oxidative potential of PM2.5 are necessary. Molecular marker chemical mass balance (MM-CMB) model and positive matrix factorization (PMF) model were the most commonly used receptor models in source apportionment studies worldwide. MM-CMB performs well in the source apportionment of organic carbon (OC) but lacks the capability of apportioning inorganic ions to sources. PMF can analyze inorganic and organic data simultaneously and can adequately estimate the contributions of sources to secondary ions. However, the simultaneous input of organic and inorganic data causes bias in the contribution results of sources that are characterized by large fractions of organic carbon and a few elemental species. A hybrid source apportionment strategy was developed incorporating MM-CMB model and PMF model to overcome the difficulties of both models. MM-CMB model was used to apportion the OC in PM2.5 to sources, and PMF model was used to analyze inorganic ions (nitrate, sulfate, and ammonia), dust, and EC. Source contributions of PM2.5 sources were estimated by reconstructing the mass of bulk chemical components apportioned to real-world sources using appropriate receptor models. The performance of the hybrid strategy, which explained 70 to 80% of measured mass concentration on average, was satisfactory. A total of nine PM2.5 sources were found with the most significant contributors to PM2.5 mass concentration being regional enriched secondary sources, mobile source, and fugitive dust. Dithiothreitol (DTT) assay was used for the quantitative measurement of oxidative potential in PM2.5. A total of 50 PM2.5 samples were selected for the oxidative potential analysis. The DTT activity of the PM2.5 had a weak linear correlation with the mass concentration of PM2.5 across the three sampling sites. Principle component analysis (PCA) results and Pearson correlation between DTT activity and PMF- resolved source contributions showed that the sources responsible for the oxidative potential of PM2.5 in Wuhan were regional enriched secondary organic and inorganic sources, and coal combustion. Although the three sources only contributed to 30% of the PM2.5 mass concentration, they were most responsible for the adverse health effects of PM2.5 in Wuhan.